Coping the Challenges While Promoting Social Justice in Mathematics Classroom - Panthi, Ram Krishna (Journal of Mathematics Education, 2023)
The purpose of this study is to explore the coping strategies applied by the teachers in the mathematics classroom to mitigate the challenges of social justice. I employed an interpretive inquiry for data collection, analysis and interpretation. I selected three mathematics teachers and their three students (one for each teacher) purposively from three public secondary schools in Kathmandu. I generated narratives through in-depth interviews with each participant. I conducted multiple layers of thematic analyses and interpretations of the narratives from the interviewed data. Altogether four themes – persuasion, watching and caring, individual treatments, and grouping emerged from the analysis of the data. This study is likely to bring awareness among teachers for socially just pedagogy.